Acute Medicine – Needs and Challenges: The Bangladesh Perspective (Journal of Medicine, 2024)
Bangladesh has an ageing population, with increased multi-morbidity and polypharmacy. Acute care is becoming more complex, with increased admission numbers and little alternative to hospital attendance and admission. Alternative models of care are discussed, that include new ways of working and use of novel training techniques including technology such as point of care testing including ultrasound. The use of ambulatory care is also proposed, with rapid access and even virtual outpatient clinics. The development of specialist acute generalists can enable other clinicians to develop more specialised skills including managing separate gastrointestinal bleeding rotas and heart attack or stroke units. Standardised care at the front door can reduce variability in practice and promote excellence in acute care for all patients. The potential pros and cons of developing an acute (internal) medicine model in Bangladesh are discussed.J MEDICINE 2024; 25: 159-165